Pacific Seascapes, Canoe Performance, and a Review of Lapita Voyaging with Regard to Theories of Migration. - Irwin, Geoffrey (Asian Perspectives: Journal of Archeology for Asia & the Pacific)
The article discusses the relevance of canoe performance, Pacific seascapes in migration theories and Lapita voyages. According to the author, navigational demand on the kind of seascapes and performances of canoe play a significant role for a successful implementation of migration activities and colonization. Moreover, the author notes that the association between the factors that affect migration activities and Lapita colonization are also examined, including technological capacities and constraints, archaeological results and competence. It also offers information on the three models of navigational optimization, including El Niño-Southern Oscillation forcing, holocene hydro-isostatic sea-level change and exploration involving strategic use of weather systems.